Acacia Senegal as an Alternative Material for Hydrogel Electrolyte Implement in Battery - et al., N.S. Alias (International Journal of Advanced Science and Technology, 2019)
In this brief review, Acacia senegal as hydrogel electrolyte for battery applications were studied. Energy storage demanding to fabricate a reliable, safe and efficient energy storage technologies to be able to use in large-scale applications. Batteries are used massively in portable electronic devices and electric vehicles because of high efficiency and energy density. Issues regarding synthetic polymer used for hydrogel electrolyte may cause toxicity, harmful substance, leakage and are non-biodegradable. Acacia senegal is a natural polymer that are non-toxic, low cost and has potential as electrolyte to apply in battery applications.